PENGARUH APLIKASI DAUN GAMAL (Gliricidia sepium (Jacq.) Kunth ex Walp.) DAN BAKTERI ENDOFIT DIAZOTROF TERHADAP SERAPAN NITROGEN DAN PERTUMBUHAN TANAMAN TEBU (Saccharum officinarum L.) - Vinalisa Damara; Dias Gustomo; Zaenal Kusuma; Sugeng Prijono (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Nitrogen (N) is very important element for the vegetative growth of sugarcane plants. Character N is easy to change shape and become unavailable. This research was aimed reduce the use of inorganic fertilizer, reduce the loss of N and increase N levels with utilizing gliricidia leaves and utilization endophytic diazotrophic bacteria or fixes nitrogen bacteria. The research used a completely randomized design with six treatments, i.e. B0i0: control (0% + 100% ZA + no added bacteria inoculation), B0i1: (0% + 100% ZA + added bacteria inoculation), B1i0 (25% + 75% ZA + no added bacteria inoculation), B1i1 (25% + 75% ZA + added bacteria inoculation), B2i0 (50% + 50% ZA + no added bacteria inoculation), B2i1 (50% + 50% ZA + added bacteria inoculation) with 5 replication. Variable observations included test of bacterial compatibility, soil total N, NH4+, NO3-, N uptake on leves, plant height, number of leaves and number of tillers. The research results showed that bacteria applied successfully entered the leaf tissue. The treatments were not significant for soil total N, NH4+, N03-, N uptake and number of tillers but significant for plant height at 6 week after planting and number of leaves at 8 and 12 weeks after planting. The organic matter of gamal leaf and bacteria endophytic diazotrophic were able to substitute ZA (ammoniu sulphate) inorganic fertilizer on sugarcane crop at 12 weeks after planting.